Lumbopelvic control and pitching performance of professional baseball pitchers - Chaudhari, A. M. W.; McKenzie, C. S.; Borchers, J. R.; Best, T. M. (The Journal of Strength and Conditioning Research, 2011)
This study assessed the correlation between lumbopelvic control during a single-leg balancing task and in-game pitching performance in Minor-League baseball pitchers. Seventy-five healthy professional baseball pitchers performed a standing lumbopelvic control test during the last week of spring training for the 2008 and 2009 seasons while wearing a custom-designed testing apparatus, the "Level Belt." With the Level Belt secured to the waist, subjects attempted to transition from a 2-leg to a single-leg pitching stance and balance while maintaining a stable pelvic position. Subjects were graded on the maximum sagittal pelvic tilt from a neutral position during the motion. Pitching performance, number of innings pitched (IP), and injuries were compared for all subjects who pitched at least 50 innings during a season. The median Level Belt score for the study group was 7°. Two-sample t-tests with equal variances were used to determine if pitchers with a Level Belt score <7° or >7° were more likely to perform differently during the baseball season, and chi-square analysis was used to compare injuries between groups. Subjects scoring <7° on the Level Belt test had significantly fewer walks plus hits per inning than subjects scoring >7° (walks plus hits per inning pitched, 1.352 ± 0.251 vs. 1.584 ± 0.360, p = 0.013) and significantly more IP during the season (IP, 78.89 ± 38.67 vs. 53.38 ± 42.47, p = 0.043). There was no significant difference in the number of pitchers injured between groups. These data suggest that lumbopelvic control influences overall performance for baseball pitchers and that a simple test of lumbopelvic control can potentially identify individuals who have a better chance of pitching success.